Fanworks Fanatisme Fandom di Comifuro Indonesia - Yossy Juwita Sari (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This research aims to understand the role of fandom in driving the growth of the fanworks market in Indonesia, specifically through the case study of Comifuro, a popular cultural event that is the center for the distribution of fan-made works. The research method used is qualitative, with a self-report approach from participants who are directly involved as creators and consumers at Comifuro since the beginning of its implementation. The results of the study show that the emotional connection between fans and copyrighted works encourages active involvement in producing and consuming fanworks. Fanworks are not only a forum for expression, but also a means of creative monetization that is socially legal even though it is legally gray. Comifuro gives creators a space for freedom of expression, bringing them together directly with audiences in an inclusive and supportive space. The surge in visitors and participants since the post-pandemic reflects the high demand for fandom content, as well as demonstrating the power of communities in supporting the creative economy. This research emphasizes the importance of recognizing the role of fans as the main motor in popular culture dynamics and community-based digital economy.